Aggregate size and glucose level affect priming sources: A three-source-partitioning study. (June 2016) - Tian, Jing; Pausch, Johanna; Yu, Guirui; Blagodatskaya, Evgenia; Kuzyakov, Yakov
Abstract: Decomposition of soil organic matter (SOM) protected within aggregates can be accelerated via priming effect (PE) by the addition of fresh substrates. However, the knowledge of the sources of mineralization and PE in aggregate size classes is absent. We applied the three-source-partitioning isotopic ( 14 C + δ 13 C) approach to determine how aggregate size classes affect the contribution of three C sources (substrate added, recent and old SOM) to CO2 efflux and PE depending on the amount of added primer. Soil from a field with 3 years of maize cropping (C4 plants) after long-term C3 vegetation was used to differentiate between recent C (C4 C; < 3 years) and old C (C3 C; >3 years). Soil samples were separated into three aggregate size classes (>2 mm, 2–0.25 mm macroaggregates and <0.25 mm microaggregates) and were incubated for 49 days after being amended with two levels of 14 C labeled glucose. The proportion of glucose mineralized to CO2 increased with decreasing aggregate size, but 14 C incorporation into microbial biomass decreased, indicating higher C use efficiency in macroaggregates compared with microaggregates. The short-time PE was positive and was accompanied by a rapid reduction of dissolved organic C. After 49 days, the PE was higher in macro-versus microaggregates at both glucose levels. Positive PE induced by a low glucose level was observed only in large macroaggregates (>2 mm), but was observed in both macroaggregates (>0.25 mm) and microaggregates (<0.25 mm) after high glucose amendment. These results indicate that SOM pools are more decomposable in macro-versus microaggregates and that the SOM pools are involved in PE according to their biochemical availability. More primed CO2 originated from recent C4 C than old C3 C in larger macroaggregates under a low glucose level. The relative contribution of recent C4 C to primed CO2 increased from macroaggregates (37.8%) to microaggregates (100%) after high glucose amendment. Therefore, increasing glucose addition stimulated the decomposition of old C3 C in macroaggregates, but not in microaggregates. This indicates that microaggregates protect SOM against decomposition better than macroaggregates, and consequently, microaggregates can be considered as a potential reservoir for long-term C sequestration. Concluding, aggregate size is crucial for SOM decomposition, and it determines the source of PE and thus the protection of sequestrated C. The effects of the added primer on C sources involved in PE depend on the aggregate size. Graphical abstract: Highlights: The proportion of glucose mineralized to CO2 decreased from micro-to macroaggregates. The PE was higher in macro-versus microaggregates at both glucose levels. High glucose stimulated decomposition of old C3 C in macroaggregates.